The prevalence and risk factors of sleep disturbances among mental health patients following hospital discharge - Mao, Wanying; Shalaby, Reham; Owusu, Ernest; Elgendy, Hossam Eldin; Agyapong, Belinda; Eboreime, Ejemai; Silverstone, Peter H.; Chue, Pierre; Li, Xin-Min; Vuong, Wesley; Ohinmaa, Arto; Taylor, Valerie; et al. (Frontiers in Public Health, 2025)
BackgroundSleep disturbances significantly impact psychological wellbeing, particularly during the critical transition when patients are discharged from psychiatric units. Despite extensive research on sleep and mental health, limited attention has been given to this transitional period.AimThis study examined the prevalence and risk factors of sleep disturbances among patients preparing for discharge from psychiatric units in Alberta, Canada.MethodsThis cross-sectional epidemiological study involved face-to-face interviews with eligible patients, followed by an online survey assessing sleep issues using the Patient Health Questionnaire (PHQ-9). Additional data on demographics, clinical information, and responses to the Generalized Anxiety Disorder (GAD-7) and World Health Organization Well-Being Index (WHO-5) were also collected.ResultsOf the 1,437 patients approached, 1,106 participated. The prevalence of sleep disturbances was 79.6%. Key factors associated with sleep issues included relationship status (Chi2 = 13.39; p = 0.01), primary mental health diagnoses (Chi2 = 61.35; p < 0.001), anxiety (Chi2 = 80.28; p < 0.001), and poor wellbeing (Chi2 = 82.18; p < 0.001) at baseline.ConclusionThe study reveals a high prevalence of sleep disturbances among patients preparing for discharge and identifies key risk factors. These findings underscore the need for targeted interventions to address sleep-related issues during the discharge transition, improving recovery outcomes and reintegration into the community.